A surface polysaccharide of Escherichia coli O111 contains O-antigen and inhibits agglutination of cells by O-antiserum. - Goldman, R C (1982)
The repeating pentasaccharide of O-antigen from Escherichia coli O111 contains galactose, glucose, N-acetylglucosamine, and colitose, the latter representing the major antigenic determinant. Phenol extraction of this strain was previously shown to release two fractions (I and II) containing O-antigen carbohydrate, and both fractions were believed to be lipopolysaccharide. We have now characterized fractions I and II and conclude that only fraction II represents lipopolysaccharide. Fraction II contains phosphate, 2-keto-3-deoxyoctonate, beta-hydroxymyristic acid, and potent endotoxin activity, whereas fraction I was deficient in all of these properties of the lipid A and core oligosaccharide regions of lipopolysaccharide. Fractions I and II each represented 50% of the total cellular O-antigen, and both were present on the cell surface. Both fractions were metabolically stable, and no precursor-product relationship existed between them. Fraction II had a number-average molecular weight of 15,800, corresponding to an average of 12 O-antigen repeats per molecule. In contrast, fraction I had a number-average molecular weight of 354,000, corresponding to an average of 404 O-antigen repeats per molecule. Before heat treatment, cells of E. coli O111 are poorly agglutinated by O-serum; although this indicates the presence of a capsule, the corresponding K-antigen was never detected. We conclude that fraction I, when present on the cell surface, inhibits agglutination of unheated cultures of E. coli O111 by O-serum because: (i) a variant strain which lacks fraction I was agglutinated by O-serum without prior heating; (ii) erythrocytes coated with purified fraction I behaved like bacteria containing fraction I in showing inhibition of O-serum agglutination; and (iii) heat treatment released fraction I and rendered bacterial cells agglutinable in O-serum.